OP15 Cost analysis in a prospective European population-based inception cohort: is there a cost-saving effect of biological therapy?. (25th January 2019) - Burisch, J; Vardi, H; Schwartz, D; Krznaric, Z; Lakatos, P L; Fumery, M; Kupcinskas, L; Magro, F; Belousova, E; Oksanen, P; Arebi, N; Langholz, E; et al.
Abstract: Background: No prospective long-term analysis of healthcare costs in patients with inflammatory bowel disease (IBD) in the era of biological treatments exists in Europe. The aim of this study was to perform a cost analysis of a pan-European inception cohort with 5 years of follow-up. Methods: The Epi-IBD cohort is a population-based inception cohort of IBD patients diagnosed from 31 centres in 20 European countries in 2010. Data were collected prospectively. Patient management was left to the discretion of the treating gastroenterologists. Data are expressed as mean costs (€/patient-year). Results: The cohort included 1362 IBD patients (Western Europe: 1, 104; Eastern Europe: 258); of which, 52% had ulcerative colitis (UC), 37% Crohn's disease (CD), and 11% IBD unclassified. Mean total expenditures per patient-year (PY) and the proportion of expenditure spent on different cost categories are shown in Tables 1 and 2. In both Eastern and Western Europe, total annual costs were highest in PY1 and then decreased (Table 1). Expenditure on biological therapy increased in this time period in both Western (PY1 €338, PY2 €410, PY3 €440, PY4 €504, and PY5 €516) and Eastern Europe (PY1 €31, PY2 €233, PY3 €355, PY4 €308, and PY5 €292). In both regions, this was paralleled by a steady decrease of costs of non-biological treatment, hospitalisation, and surgery. In a regression analysis, patients with worse disease phenotype (Figure 1) as well patients aged ≥40 years engendered higher costs. The overall outlay on biological therapy, expressed as a percentage of total expenditure, varied by age group: ≥40 years, 29%; 41–60 years, 21%; and ≥61 years, 11%. Conclusions: In this population-based inception cohort of unselected IBD patients, overall direct expenditure on healthcare decreased over a 5-year follow-up period in parallel with remarkably increasing expenditure on biologics, particularly in CD patients, and decreasing expenditure on standard medical treatments, surgery, and hospitalisation. Despite their known high-acquisition charges, these data indicate a cost-saving effect of biological medications.